2013
DOI: 10.1007/s10989-013-9370-z
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in the Mechanical Properties of Human Fibroblasts and Its Prospective Reversal After Anti-Wrinkle Tripeptide Treatment

Abstract: One of an essential characteristic of human skin are time dependent mechanical properties. Here, we demonstrate that stiffness of human dermal fibroblast correlates with age and it can be restored after anti-wrinkle tripeptide treatment. The stiffness of human fibroblasts isolated from donors of 30-, 40- and 60 years old were examined. Additionally the effect of anti- wrinkle tripeptide of latter cells was investigated. The atomic force microscopy measurements were performed on untreated fibroblast as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 26 publications
4
38
0
Order By: Relevance
“…Indeed, numerous studies have demonstrated that there is a strong correlation between age and cytoplasmic stiffness (i.e., cytoplasmic compliance or deformability is reduced with age) ( Figure 2 ). Studies that have applied AFM to adherent human cells [epithelial cells (37, 42, 73), fibroblasts (38), and cardiac myocytes (40)] seeded on flat substrates have shown that cells consistently respond to mechanical activation with a stiffening response as a function of increasing age. This suggests that age-dependent cytoplasmic stiffening is not cell-type specific.…”
Section: Aging and Cell Mechanicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, numerous studies have demonstrated that there is a strong correlation between age and cytoplasmic stiffness (i.e., cytoplasmic compliance or deformability is reduced with age) ( Figure 2 ). Studies that have applied AFM to adherent human cells [epithelial cells (37, 42, 73), fibroblasts (38), and cardiac myocytes (40)] seeded on flat substrates have shown that cells consistently respond to mechanical activation with a stiffening response as a function of increasing age. This suggests that age-dependent cytoplasmic stiffening is not cell-type specific.…”
Section: Aging and Cell Mechanicsmentioning
confidence: 99%
“…In efforts to better understand how to potentially reduce these age-dependent mechanical dysfunctions in cells and tissues, studies have been geared toward assessing the possibility of reversing the mechanical phenotypes of cells derived from elderly individuals (38, 42). Due to the dominating effects of the actin cytoskeleton and the increased F-actin content (38, 39) observed in cells from older donors (i.e., fibroblasts, cardiac myocytes, and red blood cells), a widely studied target for possible phenotypic reversal is the use of pharmacological agents that affect F-actin.…”
Section: Aging and Cell Mechanicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hara [25] suggested that the Young's Modulus of the epidermis layer of the skin increases with age, while that of the dermis layer remains constant with age. Molak [26] performed experiments using indentation technique and found out that the Young's Modulus increased with age and remained unaltered for the indenter depths of 200 and 600 nm respectively.…”
Section: Journal Of Ageing Sciencementioning
confidence: 99%